2014
DOI: 10.2139/ssrn.2423801
|View full text |Cite
|
Sign up to set email alerts
|

Chocolate Milk Consequences: A Pilot Study Evaluating the Consequences of Banning Chocolate Milk in School Cafeterias

Abstract: Objectives: Currently, 68.3% of the milk available in schools is flavored, with chocolate being the most popular (61.6% of all milk). If chocolate milk is removed from a school cafeteria, what will happen to overall milk selection and consumption?Methods: In a before-after study in 11 Oregon elementary schools, flavored milk-which will be referred to as chocolate milk-was banned from the cafeteria. Milk sales, school enrollment, and data for daily participation in the National School Lunch Program (NSLP) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…33 Eliminating the added sugars from milk may increase milk wastage, resulting in fewer ounces consumed per day. 34,35 Outside of school, whole and 2% milk varieties comprise nearly three-quarters of the milk consumed by children, whereas 1% and nonfat milk combined account for only 20%. 33 Inside schools, flavored milk represents more than 70% of all milk consumed; 38.5% of milk, however, is nonfat and 51% is 1% fat, a substantial decrease in saturated fat and calories relative to consumption patterns outside of school.…”
Section: Beverage Requirementsmentioning
confidence: 99%
“…33 Eliminating the added sugars from milk may increase milk wastage, resulting in fewer ounces consumed per day. 34,35 Outside of school, whole and 2% milk varieties comprise nearly three-quarters of the milk consumed by children, whereas 1% and nonfat milk combined account for only 20%. 33 Inside schools, flavored milk represents more than 70% of all milk consumed; 38.5% of milk, however, is nonfat and 51% is 1% fat, a substantial decrease in saturated fat and calories relative to consumption patterns outside of school.…”
Section: Beverage Requirementsmentioning
confidence: 99%
“…Of the students who consumed lunch served as part of the National School Lunch Program, two thirds chose chocolate over white milk . Previous studies have shown that children who drank flavored milk consumed more total milk overall compared with children who consumed white milk and there was significantly less wastage of milk …”
mentioning
confidence: 99%
“…While there is some uncertainty on how chocolate milk selection over plain milk selection affects health status, chocolate milk contains about twice the sugar as plain milk. Attempts at eliminating chocolate milk and only offering plain milk in school cafeterias have led to increased plain milk purchase, but with a 10% to 26% overall milk purchase decrease and a decrease in consumption [25,26]. In our intervention, we successfully increased plain milk and even had a modest increase in overall milk purchase.…”
Section: Discussionmentioning
confidence: 87%